You say it is physical, I say it is functional; let us call the whole thing off! Simulation: an application divided by lack of common language. (2nd September 2020) - Roberts, Aaron P. J.; Stanton, Neville A.; Plant, Katherine L.; Fay, Daniel T.; Pope, Kiome A.
Abstract: Simulations are utilised in various domains for purposes of training, research, education and entertainment. Continuing technological advancement, along with a striving for higher levels of immersion, transfer and user satisfaction has driven the design of increasingly complex simulators. Economic viability, portability and usability of such simulators have simultaneously decreased, prompting a contemporary examination of simulator fidelity. Simulator fidelity is a poorly understood construct, notorious for its lack of clear definition. A wide range of terminology is used interchangeably, with subtle differences in the functionality of the language used not always clearly outlined. In the current manuscript, a comprehensive review of the literature informs clear definitions of fidelity, validity and transfer; the terms used are included in a definitions table and their connectivity outlined in a knowledge tree. The aim is to promote usage of clearly interpretable standardised terminology by professionals and researchers alike. The boundaries of the current work are acknowledged. It is suggested that future research should examine constructs such as fidelity, transfer and validity in relation to computational, robotic and automation simulation. The most immediate extension of the current work should capture a requirement to develop effective training interventions to govern operator use of automation using interactive simulation.